(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The First Translations of the Bible into Romanian and Their Influence on the Unity of the National Language The Celebration of the Centenary of the Great Union gives us the opportunity to reflect on the factors that have sustained the perpetuity of the Romanian people over the centuries. One of these factors is the common language used by the Romanians in all three historical provinces and which has ensured the communication and transfer of ideas and values. One of the causes mentioned by the researchers regarding the unity of the Romanian language is the fact that, in the 16th and 17th centuries, the Bible was translated into Romanian. The translation of the Bible would, according to some scholars, have had a major impact on the uniformity of the Romanian literary language. In this study, we studied, in particular, the biblical prints of the Deacon Coresi and the Bible of 1688. Although these works had an influence that can not be denied, recent studies have highlighted a diminished role. The research included an analysis of the production process, as well as the social and political conditions and gave us a concrete image, helping us get out of the intuitive general picture that was originally proposed. However, when we speak of the influence of the Bible on the Romanian language, we must take into account not only the spread of books, but also the possibility of listening to them. At that time, most did not read Scripture, but listened it in the Church.